2015
DOI: 10.3166/ges.17.273-288
|View full text |Cite
|
Sign up to set email alerts
|

Théorie du développement territorial

Abstract: La notion de développement territorial, qui évoque la possibilité d'évolutions plus ou moins autonomes ou indépendantes de celle des nations, voire des régions, s'impose. Avant de mettre en oeuvre des politiques, ou de conseiller les décideurs et acteurs des dynamiques locales, il est utile de fonder la légitimité de ce concept, de définir plus précisément sa signification et ses implications, ainsi que d'apporter une pierre à l'édifice théorique en construction. C'est l'objet de ce texte. Après avoir décrit l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 33 publications
0
4
0
18
Order By: Relevance
“…These seminars allowed the collective production of a case study analysis grid and revealed the four dimensions proposed in this article. They complement the main focal points of research in the human and social sciences on territorial development during four successive periods (Jean 2008 ; Pike et al 2006 ; Torre 2015 ): specialization since the 1980s, innovation since the 1990s, adaptation since the 2000s and transition since the 2010s.…”
Section: Introductionmentioning
confidence: 84%
“…These seminars allowed the collective production of a case study analysis grid and revealed the four dimensions proposed in this article. They complement the main focal points of research in the human and social sciences on territorial development during four successive periods (Jean 2008 ; Pike et al 2006 ; Torre 2015 ): specialization since the 1980s, innovation since the 1990s, adaptation since the 2000s and transition since the 2010s.…”
Section: Introductionmentioning
confidence: 84%
“…El concepto de desarrollo territorial integrado (Moulaert & Sekia, 2003;Pike, Rodríguez Pose, & Tomaney, 2006;Vázquez Barquero, 2007;Torre, 2015) aspira a superar las visiones economicistas que igualan desarrollo local con crecimiento económico y reducen lo económico a variables macro como el producto interior bruto o la renta media por habitante. Mientras el crecimiento significa, nada más, ganancia de tamaño, el desarrollo conlleva la adquisición de nuevas capacidades.…”
Section: Capitalismo Y Territorio O El Proyecto Estructural-contextualunclassified
“…The result is a reconsideration and broadening of the analysis of territorial development processes (Torre, ). If they are based on technological and organizational innovation drivers, as has been pointed out for a long time by approaches to local productive systems for example, they are also based on innovations of a completely different nature, social and institutional ones.…”
Section: Crossed Explorations and Involvement Of Other Social Sciencesmentioning
confidence: 99%
“…The result is a reconsideration and broadening of the analysis of territorial development processes (Torre, 2015).…”
Section: Territorial Governance and Territorial Developmentmentioning
confidence: 99%